Strategies For Handling Slum Areas In The City Of Ambon - Sakir, Ahmad Rosandi (PT. Anagata Sembagi Education, 2024)
The study is dedicated to comprehending the strategies employed for addressing slum areas in the city of Ambon, with the goal of contributing to urban development and enhancing the living conditions of its residents. Employing a qualitative descriptive research design, this research seeks to delve into the various strategies implemented to handle slum areas in Ambon. The qualitative approach enables an in-depth exploration of the multifaceted aspects involved in addressing and preventing slum settlements. In conclusion, the spatial planning and slum prevention initiatives in Ambon exemplify a comprehensive and adaptable approach to urban development. These initiatives underscore the city's dedication to sustainability, environmental conservation, and the active involvement of the community. While effectively addressing immediate challenges related to slum areas, these plans also serve as a groundwork for Ambon's future growth and resilience amid the ever-changing dynamics of urban development. The research findings provide valuable insights into the strategies employed by Ambon to create a more livable and sustainable urban environment, demonstrating a commitment to the well-being of its residents and the long-term prosperity of the city.